Evaluación de la vida útil de maíz (Zea mays) mínimamente procesado, utilizando dos tipos de embalaje - Rojas Linares, Mauricio Daniel (2016)
This research project was developed at the State University of Bolivar, in Agroindustrial Engineering, in which the life of sweet corn (Zea mays) variety INIAP 111 "Guagal Mejorado" minimally processed using two types of packaging (polyvinylchloride and low density polyethylene); underwent three pre cooking times: 15, 20 and 25 minutes and two pre cooking temperatures: 60 and 65 ° C to prolong their useful life; the same was evaluated by subjecting 24 treatments to experimental measurements of pH, acidity, Brix and weight for 9 days storage at refrigeration temperatures (4 ° C). These data were within normal parameters according to data reported in literature. It also contrasted with microbiological analysis of E coli and yeast and mold, results were within the Ecuadorian INEN technical standards. Tables ADEVA obtained were considered with reference analysis on days 1, 5 and 9 of storage; in which all treatments were within normal parameters established in literature. Which the ADEVA tables had in common that the treatment was A3B2C2 correspondent to 25 minutes of pre cooking + packaging PVC + 65 ° C temperature pre cooking was the best in relation to assessed by the tasters and retaining better the physical, chemical and microbiological characteristics. Cost benefit analysis established that un applying this treatment to an amount of 500 grams of corn a profit of 1.20 USD you get.